Distribution and severity of hypoxic–ischaemic lesions on brain MRI following therapeutic cooling: selective head versus whole body cooling. Issue 5 (29th August 2012) - Sarkar, Subrata; Donn, Steven M; Bapuraj, Jayapalli R; Bhagat, Indira; Barks, John D
Abstract : Background: Whole body cooling (WBC) cools different parts of the brain uniformly, and selective head cooling (SHC) cools the superficial brain more than the deeper brain structures. In this study, the authors hypothesised that the hypoxic–ischaemic lesions on brain MRI following cooling would differ between modalities of cooling. Aim: To compare the frequency, distribution and severity of hypoxic–ischaemic lesions on brain MRI between SHC or WBC. Methods: In a single centre retrospective study, 83 infants consecutively cooled using either SHC (n=34) or WBC (n=49) underwent brain MRI. MRI images were evaluated by a neuroradiologist, who was masked to clinical parameters and outcomes, using a basal ganglia/watershed (BG/W) scoring system. Higher scores (on a scale of 0 to 4) were given for more extensive injury. The score has been reported to be predictive of neuromotor and cognitive outcome at 12 months. Results: The two groups were similar for severity of depression as assessed by a history of an intrapartum sentinel event, Apgar scores, initial blood pH and base deficit and early neurological examination. However, abnormal MRI was more frequent in the SHC group (SHC 25 of 34, 74% vs WBC 22 of 49, 45%; p=0.0132, OR 3.4, 95% CI 1.3 to 8.8). Infants from the SHC group also had more severe hypoxic–ischaemic lesions (median BG/W score: SHC 2 vs WBC 0, p=0.0014). Conclusions: Hypoxic–ischaemic lesions on brain MRI following therapeutic cooling were more frequent and more severe with SHC compared with WBC.